2019
DOI: 10.3390/ani9110876
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of In Ovo Delivered Prebiotics on Growth Performance, Meat Quality and Gut Health of Kuroiler Chickens in the Face of a Natural Coccidiosis Challenge

Abstract: Simple SummaryThe management of coccidiosis in poultry farms is mainly dependent on the use of anticoccidial drugs. Development of resistance to existing anticoccidial drugs coupled with restrictive use of antibiotics to control secondary bacterial infections following the ban on antibiotics, stresses the urgent need to explore alternative strategies for maintaining intestinal functionality in chickens for improved productivity. Prebiotics have been proposed as a solution to the intestinal problems of poultry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
(72 reference statements)
1
16
0
Order By: Relevance
“…At day 42, a significant, 89% reduction in oocysts was observed after the lupin RFO treatment in ovo. This is in line with the study of Angwech et al [10] where another prebiotic, the galactooligosaccharides injected in ovo on day 12 of egg incubation, reduced the shedding of oocysts in excreta of Kurolier (slow growing) chickens after 6 weeks of rearing.…”
Section: The Mitigation Of Natural Environmental Pathogenic Infectionsupporting
confidence: 91%
See 2 more Smart Citations
“…At day 42, a significant, 89% reduction in oocysts was observed after the lupin RFO treatment in ovo. This is in line with the study of Angwech et al [10] where another prebiotic, the galactooligosaccharides injected in ovo on day 12 of egg incubation, reduced the shedding of oocysts in excreta of Kurolier (slow growing) chickens after 6 weeks of rearing.…”
Section: The Mitigation Of Natural Environmental Pathogenic Infectionsupporting
confidence: 91%
“…The effects of reducing parasitic oocysts by the prebiotics are likely to provide benefits to the health of the flock [10]. The oocyst shed in broilers droppings.…”
Section: The Mitigation Of Natural Environmental Pathogenic Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated a marked increase in the density of muscle fibres associated with the administration of prebiotics [21,24] or synbiotics [24,25], which was associated with higher meat tenderness. The positive effect of a prebiotic on fatty acid composition in chicken meat was reported by Angwech et al [26], but a study by Tavaniello et al [22] did not confirm this finding. On the other hand, Maiorano et al [21] reported that the supplementation with a prebiotic had no significant effect on the content of intramuscular fat, while Dankowiakowska et al [27] found a higher content of intramuscular fat, but in a study by Tavaniello et al [22] this parameter was lower.…”
Section: Introductionmentioning
confidence: 85%
“…At the present moment, different molecules, compounds, bioactive substances, and active principles have been investigated and are still under investigation [5]. Among them, several classes of feed additives are now available, including probiotics [6,7], prebiotics [8,9], organic acids [10,11], and phytobiotics [12]. Although the benefits of such additives have been proven in most cases, there is still a lack of clarity on their effects, as evidenced by some contrasting results in different trials.…”
Section: Introductionmentioning
confidence: 99%